Research trends on the use of mobile devices in physics experiments: A bibliometric study - Le, Huy Thanh; Bao, Nguyen Quach Nguyen; Ha, Linh Phan Thi; Thi, Lanh Huynh (Edelweiss Applied Science and Technology, 2026)
This study aims to systematically map research trends on the use of mobile devices in physics experiments. A bibliometric approach was employed, using a refined dataset of 526 journal articles indexed in Scopus from 1963 to 2026. The analysis was conducted with VOSviewer and Bibliometrix to examine publication growth, scholarly impact, geographic distribution, and thematic evolution. The findings reveal a three-stage development: emergence, consolidation, and rapid expansion, with a significant increase in publications and citations after 2010. While Q2 journals such as Physics Education and The Physics Teacher lead in productivity, Q1 journals like Computers & Education show the highest impact, indicating a productivity–impact decoupling. The United States and China dominate research output, whereas Spain demonstrates strong international collaboration. Three main research themes are identified: pedagogical applications, smartphone-based sensor measurements, and hybrid simulation approaches. In conclusion, the field has experienced substantial growth and diversification, highlighting the growing role of mobile technologies in physics education. These results provide practical implications for educators and researchers in identifying research directions, fostering collaboration, and enhancing the integration of mobile devices in physics learning.